5-Bromouracil and 5-bromouracil-histidine complexes with metal(III) ions and their antitumour activity - Singh V.P.; Singh A.; Narang K.K.; Bhattacharya D. (My University, 2025)
Complexes of the [AILCl2], [ML(OH)Cl] and [M′LL′(H2O)Cl] type, where HL = 5-bromouracil; HL′ = histidine; M = CrIII or FeIII and M′ = Al III, Cr or FeIII were synthesized and characterized. The complexes are polymers with high temperature decomposition points and are insoluble in H2O and common organic solvents. 5-Bromouracil is coordinated to the metal ion through the O atom of C(4)=O and the N atom of N(1), while histidine coordinates through the O atom of -CO2- and the N atom of the -NH2 groups. The μeff values, electronic spectral bands and e.s.r. spectra suggest a polymeric six-coordinate spin-free octahedral stereochemistry for the Cr III and FeIII complexes. The in vivo antitumour effect of 5-bromouracil and its complexes was examined on C3H/He mice versus P815 murine mastocytoma. As is evident from their T/C values CrIII and FeIII complexes display significant and higher antitumour activity compared to 5-bromouracil while the AlIII complexes show lower activity. The in vitro results of the complexes on the same cells indicate that CrIII and FeIII complexes show higher inhibition on 3H-thymidine and 3H-uridine incorporation in DNA and RNA replication, respectively.